2011
DOI: 10.1101/gr.124370.111
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genetic and gene expression evidence into genome-wide association analysis of gene sets

Abstract: Single variant or single gene analyses generally account for only a small proportion of the phenotypic variation in complex traits. Alternatively, gene set or pathway association analyses are playing an increasingly important role in uncovering genetic architectures of complex traits through the identification of systematic genetic interactions. Two dominant paradigms for gene set analyses are association analyses based on SNP genotypes and those based on gene expression profiles. However, gene–disease associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 91 publications
0
86
0
Order By: Relevance
“…In parallel, genetic association studies were carried out and showed the association of OTSC with polymorphisms in the COL1A1, TGFB1, BMP2, BMP4, and RELN genes in multiple populations (McKenna et al, 1998;Thys et al, 2007a;Schrauwen et al, 2008;Schrauwen et al, 2009;Khalfallah et al, 2010;Khalfallah et al, 2011;Priyadarshi et al, 2013). Gene expression profiling of disease tissue compared to controls has been suggested as a method to investigate the genetic basis of complex disorders (Xiong et al, 2012). Some of the studies have reported reduced or missing OPG expression in the otosclerotic tissue (Karosi et al, 2011;Potocka-Baklazec et al, 2014) but the exact mechanism that controls the altered OPG expression in OTSC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, genetic association studies were carried out and showed the association of OTSC with polymorphisms in the COL1A1, TGFB1, BMP2, BMP4, and RELN genes in multiple populations (McKenna et al, 1998;Thys et al, 2007a;Schrauwen et al, 2008;Schrauwen et al, 2009;Khalfallah et al, 2010;Khalfallah et al, 2011;Priyadarshi et al, 2013). Gene expression profiling of disease tissue compared to controls has been suggested as a method to investigate the genetic basis of complex disorders (Xiong et al, 2012). Some of the studies have reported reduced or missing OPG expression in the otosclerotic tissue (Karosi et al, 2011;Potocka-Baklazec et al, 2014) but the exact mechanism that controls the altered OPG expression in OTSC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, based on the expression values of module genes, we analyzed the correlation between module genes and the DCM disease state using a toolset of Gene Set Association Analysis for RNA-Seq with Sample Permutation (GSAASeqSP, http://gsaa.unc.edu) [38], and the module with a nominal p-value of <0.05 was considered to be significantly correlated with the DCM disease state. Furthermore, according to the core enrichment gene obtained from GSAASeqSP, we screened key lncRNAs and constructed the lncRNA regulatory network on the basis of the WGCNA module.…”
Section: Correlation Analysis Of Wgcna Modules and Dcm Disease Statementioning
confidence: 99%
“…The Fisher's exact test found that there was not a greater than expected number of SNPs within the differentially expressed genes within any of the strains. However, we anticipate that we will use the Gene Set Association Analysis-SNP (GSAA-SNP) software (30) to further investigate possible relationships between the SNPs identified within each strain and the differentially expressed gene data sets. This work could be translated into a greater ability to predict whether there are additional human populations that might be more susceptible to the effects of PB and whether the response to PB varies by genotypic differences at other loci beyond those for detoxification enzymes, such as butyrylcholinesterase and paraoxonase.…”
Section: Effects Of Genetic Variation On the Response To Pyridostigmimentioning
confidence: 99%